Keputusan Bekerja Perempuan sebagai Buruh Angkut di Pasar Badung dalam Perspektif Peran Ganda - Dewi, Kadek Enna Pebrianti; Indrayani, Luh (Universitas Pendidikan Ganesha, 2025)
This study aims to determine the reasons why women decide to work as porters, strategies for balancing dual roles, and the impact of working as porters on the economic life and family welfare of women porters in Badung Market. This research uses a qualitative approach with a case study type. Data were collected through observation, interviews with five main informants, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study show several factors that cause women to decide to work as porters, namely economic factors, flexible working hours, education, age, and proximity to the workplace. The strategy of women porters to balance their dual roles is carried out by dividing a balanced time between work at home and work in the market and dividing domestic duties with the family. This work has an impact on family economic life such as increasing family income to meet family economic needs.